Specialistično proučevanje zakonsko zaščitenih narodnostnih manjšin v Sloveniji do obdobja državne osamosvojitve - Kristen, Samo (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The contribution discusses the historiography of specialised research of legally protected minorities in the Slovenian territory in three time periods:from mid-1920s, a period which coincides with the first institutional beginnings of such research in the Kingdom of Yugoslavia, and extending to theSecond World War and its aftermath, and to the disintegration of the Yugoslav federation in the mid-1990s, which brought about the creation of an independent Slovenian state. Contrary to the situation regarding the Slovenianminority populations in Italy, Austria, and Hungary, the research of legally acknowledged national minorities has not always been an obvious, and even less so a privileged theme in the tradition of the Slovenian national question. Elements of such research, which were particularly "interesting for the then authorities" in the Kingdom of Yugoslavia, were present in the activity of the Minority Institute in Ljubljana from mid-1920s to early 1940s.After a relatively long interruption of activity, the research focus on the Hungarian and the Italian minorities intensified substantially. It diversified interdisciplinary (and institutionally) in the early 1960s and expanded constantly in the 1970s and 1980s, reaching its unprecedented quantitative climax a few years after Slovenia's independence, before its accession to the European Union.
Keywords: Slovenia; Slovenija; narodne manjšine; narodnostno vprašanje; Slovenci; Slovenes; Madžari; zgodovinski pregledi